Contrast Enhanced Ultrasound in the Diagnosis and Evaluation of the Efficiency of Chemotherapy in Patients with Colorectal Liver Metastases - E. V. Kovaleva; G. T. Sinyukova; T. Yu. Danzanova; P. I. Lepedatu; E. A. Gudilina; G. F. Allakhverdieva (Вестник рентгенологии и радиологии)
Objective: to determine the possibilities of contrast-enhanced ultrasound (CEUS) in identifying and evaluating the efficiency of chemotherapy in patients with colorectal liver metastases (CLM).Material and methods. The investigation enrolled 28 patients with CLM. The patients were divided into two groups: Group 1 – 15 pretreatment patients; Group 2 – 13 posttreatment patients with process stabilization. All the patients underwent standard B-mode ultrasound of the liver and that using the contrast agent SonoVue ® (Bracco, Italy), by recording and estimating the parameters of the intensity-time curve (CIV). Liver CEUS assesses the nature of contrasting metastases in three phases (arterial, venous, and delay ones).Results. The investigators identified three types of contrast agent accumulation in CLM in the arterial phase: along the periphery of the lesions (in 60% of the patients of Group 1, in 76.9% in Group 2), homogeneously over the entire volume (in 26.7% in Group 1 and in 0.08% in Group 2), in parallel with intact liver parenchyma (13.3% in Group 1 and 23.02% in Group 2). In the delay phase, more metastases were detected in 4 cases (14.3%). Estimation of CIV parameters showed a difference at the beginning of contrast enhancement stages between the patients in both groups. Group 1 exhibited the early contrasting of liver metastases (19.3 sec); Group 2 displayed the late washout of a contrast agent (65.9 sec).Conclusion. CEUS versus B-mode ultrasound improves the imaging of liver metastases. The change in the vascular architectonics and hemodynamics in CLM after chemotherapy is reflected in the alteration of the rate of contrast accumulation and washout from the metastases, which allows CEUS to be used in the evaluation of the efficiency of this treatment.